Our beautiful mess - Parks, Adele (Park Row Books, 2026)
"Connie can't wait to have all her daughters back home for Christmas. It's not just the excitement of the girls being together under one roof; uni student Fran is bringing a new boyfriend to stay. The empty nest will once again be full of friends, family and young love. Yet from the moment she sees Zac, Connie feels a deep unease. Zac reminds her of the worst mistake she has ever made: a man whose charm and good looks nearly destroyed her marriage. Then, Fran announces she's pregnant. Reeling from Fran's news and terrified that her past might threaten her family's future, Connie desperately tries to navigate a path forward. But there's a much greater menace looming, because she's not the only one who has something to hide. Someone in the house has another devastating secret. A deception which will put everyone Connie loves in shocking danger, and one of them will pay the ultimate price."-- Provided by publisher.